The Development of a Cost Effective Engine Dynamic Signal Monitoring and Diagnostic System - Tjong, J.S. Y.; Chang, D. K.; Mathias, D.; Zena, S. A.; Runge, J. R.; Reif, Z. (Canadian Acoustics, 1993)
This paper describes the development of a cost effective engine dynamic signal monitoring and diagnostic system for use in a high volume engine manufacturing plant as well as in a research environment for development of new engine components.